IT'S TIME TO THINK OUTSIDE THE COMPUTATIONAL BOX. - Kugel, Peter (Communications of the ACM, 2005)
The article focuses on how to make computers understand people by programming them. Computers would be a lot easier to deal with if they could somehow try to understand people. The problem is that computers need programmers to help them understand people. There are user manuals and programming languages to help people program computers. Computers can be programmed by giving them examples of what task they have to do and letting them develop their own programs to do the task. It has been called programming by example. It may not be possible to get computers to do a decent job of developing programs from examples if the usage is limited to computations. It would be easier to allow them to use algorithms from outside the computational toolbox. Overcoming inefficiency is probably more important than dealing with incompleteness. The rate at which an algorithm gets to the right program might be speeded up by either using knowledge about particular application areas or allowing the algorithms to rearrange their lists as more information about the current problem comes in.